Disease alleviating effects following prophylactic lemon and coriander essential oil treatment in mice with acute campylobacteriosis - Mousavi, Soraya; Weschka, Dennis; Bereswill, Stefan; Heimesaat, Markus M. (Frontiers in Microbiology, 2023)
Given the worldwide increasing prevalence of human Campylobacter jejuni infections and the emergence of multi-drug resistant enteropathogenic strains, antibiotic-independent approaches applying non-toxic natural compounds for the treatment and prophylaxis of campylobacteriosis appear utmost desirable. In our placebo-controlled intervention study we surveyed potential dis-ease-alleviating including anti-pathogenic and immune-modulatory effects upon prophylactic oral application of lemon-essential oil (LEM-EO) and coriander-essential oil (COR-EO) in experi-mental acute campylobacteriosis. Therefore, secondary abiotic IL-10-/- mice were orally chal-lenged with either LEM-EO or COR-EO starting seven days prior peroral C. jejuni infection. Six days post-infection, slightly lower pathogen loads could be assessed in the colon of mice from the LEM-EO as opposed to COR-EO cohort if compared to placebo counterparts. Prophylactic application of both EOs improved the clinical outcome of acute campylobacteriosis which was paralleled by less distinct pathogen-induced colonic epithelial cell apoptosis. Moreover, mice subjected to LEM-EO and COR-EO prophylaxis displayed lower colonic numbers of macro-phages/monocytes and of T lymphocytes, respectively, whereas in both verum groups, basal IL-6 and IFN-γ concentrations were measured in mesenteric lymph nodes on day 6 post-infection. Strikingly, oral challenge with either EO resulted in diminished secretion of distinct pro-inflammatory mediators in the kidney as well as serum samples derived from infected mice. In conclusion, results from our preclinical in vivo study provide evidence that LEM-EO and COR-EO constitute promising prophylactic measures to prevent severe campylobacteriosis which may help to reduce the risk for development of secondary sequelae in C. jejuni infected individuals.